2011
DOI: 10.1002/ibd.21469
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-based therapeutic delivery of prohibitin to the colonic epithelial cells ameliorates acute murine colitis

Abstract: Introduction-Intestinal epithelial expression of anti-oxidants and NF-κB contribute to mucosal barrier integrity and epithelial homoestasis, two key events in the pathogenesis of inflammatory bowel disease. Genetic restoration of intestinal epithelial prohibitin 1 (PHB) levels during experimental colitis reduces the severity of disease through sustained epithelial anti-oxidant expression and reduced NF-κB activation. To determine the therapeutic potential of restoring epithelial PHB during experimental colitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…Another aspect of Phb is its therapeutic potential. Previously, it has been shown that nanoparticle-based therapeutic delivery of Phb to the colonic epithelial cells ameliorates acute murine colitis (6,11). Correspondingly, the administration of Phb to the colonic mucosa of patients with UC may be a new therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another aspect of Phb is its therapeutic potential. Previously, it has been shown that nanoparticle-based therapeutic delivery of Phb to the colonic epithelial cells ameliorates acute murine colitis (6,11). Correspondingly, the administration of Phb to the colonic mucosa of patients with UC may be a new therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, it has been shown that Phb expression is decreased in the colonic mucosa of patients with inflammatory bowel disease compared to that of healthy controls. It has also been suggested as a therapeutic agent in experimental colitis models (2,(8)(9)(10)(11). Increased levels of Phb-2 and Slp-2 are related to poor prognosis in different types of malignancies (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…The group of Laroui et al has performed numerous studies in this area. [63][64][65][66] The negatively charged siRNA combines with the positively charged PEI to form the internal aqueous phase. The internal aqueous phase is mixed with PLA or PLA derivatives in an organic phase, typically dichloromethane, to generate a water/oil (W/O) emulsion.…”
Section: Pla-based Nanoparticlesmentioning
confidence: 99%
“…63 A similar synthetic method for PLA nanoparticles was introduced by forming nanoparticles encapsulated in recombinant human prohibitin ameliorating acute murine colitis. 64 Prohibitin is a type of positive therapeutic protein for attenuating UC and CD. Expression of prohibitin decreases the oxidative level and TNF-α-stimulated nuclear factor-κB (NF-κB) activation in intestinal epithelial tissue.…”
mentioning
confidence: 99%
“…Pro-inflammatory cytokines such as TNFa and oxidative stress induced by exogenous H 2 O 2 decrease expression of intestinal epithelial PHB in vivo and in vitro [37,42]. Restoration of colonic epithelial PHB expression using genetic manipulation (villin-PHB transgenic mice) or therapeutic delivery to the colon via nanoparticle or adenovirus protected mice from experimental colitis [43,44]. Our recent data suggest that epithelial PHB sustains anti-oxidant expression [44] and has anti-inflammatory properties such as reducing TNFa-stimulated NF-kB activation [42].…”
Section: Introductionmentioning
confidence: 99%